Intraoperative Monitoring Cerebral Blood Flow During the Treatment of Brain Arteriovenous Malformations in Hybrid Operating Room by Laser Speckle Contrast Imaging - Tao, Sicai; Zhang, Tingbao; Zhou, Keyao; Liu, Xiaohu; Feng, Yu; Zhao, Wenyuan; Chen, Jincao (Frontiers in Surgery, 2022)
Background: Hemodynamic changes caused by hybrid surgery for brain arteriovenous malformations (bAVM) are usually related to long-term lesion from “blood stealing”. There are currently no viable low-cost, noninvasive procedures for assessing cerebral perfusion in the operating room. The aim of this study was to investigate the use of intraoperative laser speckle contrast image (LSCI) software in AVM surgery. Methods: 14 patients underwent surgery with LSCI were collected in Zhongnan Hospital of Wuhan University. To analyze the hemodynamic features of AVM and the influence on the peripheral cortex of AVM embolization and resection, we assessed the transit time between feeding arteries and drainage veins by intraoperative digital subtraction angiography (DSA). Meanwhile LSCI was performed at pre-embolization, post-embolization and after complete resection of bAVM. Results: In this study, the transit time of bAVM before and after embolization was compared, the transit time before embolization were significantly shorter than that after embolization (P<0.05). We also got good visualization of relative CBF in addition to flow imaging in the cortical vasculature round bAVM with LSCI. FLUX of post-surgery was significantly higher than pre-embolization (P < 0.01). Conclusion: Hemodynamic variable assessment plays an important role in the resection AVM in the hybrid operative room and LSCI may be used to visualize and evaluate cortical cerebral blood flow to detect pathological hyperperfusion in real-time with good spatial–temporal resolution in a sensitive and continuous, non-invasive mode.